The Differential Impact of Emotional Support on Social Problem‐Solving and Mental Health Among Latina Immigrant Survivors of Adverse Childhood Experiences. - Lopez, Laura Mata; Smith, Owen; Sanchez‐Roman, Maria Jose; Escobar‐Acosta, Lia; Alvarez, Carmen (Research in Nursing & Health, 2026)
Adverse childhood experiences (ACEs) are often positively associated with mental health conditions. We examined whether emotional support attenuates the association between ACE clusters and both social problem solving and mental health assessments (depression, anxiety, post‐traumatic stress disorder (PTSD) symptoms). A convenience sample of 336 Latina immigrant women completed questionnaires about their ACEs, emotional support, social problem‐solving, and depression, anxiety, and PTSD symptoms. Using PROCESS SPSS Macro version 4.0 we conducted four separate moderation analyses. We identified 5 ACEs clusters from our sample (n = 336): Global ACEs (15.5%), Community Violence and Physical Abuse (23.8%), Physical and Emotional Abuse (21.4%), Household Dysfunction with Physical and Emotional Abuse (16.7%), and Low ACEs (22.6%). Emotional support served as a protective moderator with differential effects, providing the greatest benefit to women who experienced high levels of abuse. For social problem‐solving abilities, significant interactions emerged for the Physical and Emotional Abuse and Household Dysfunction clusters, indicating that as emotional support increases, the difference in social problem‐solving between these high‐ACE clusters and the Low ACEs cluster decreased. For PTSD symptoms, women in the Global ACEs cluster showed significantly higher symptoms than the Low ACEs group when emotional support was low. The clusters did not differ at high emotional support levels, indicating that adequate social support can reduce the negative effects of ACEs on both PTSD symptoms and effective problem‐solving. These findings underscore the need for trauma‐informed, culturally responsive care models that integrate ACE screening and guide future interventions to strengthen social support networks for ACE survivors.